2019
DOI: 10.1136/bmjopen-2018-027583
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a therapist-guided, parent-assisted remote digital behavioural intervention for tics in children and adolescents—‘Online Remote Behavioural Intervention for Tics’ (ORBIT) trial: protocol of an internal pilot study and single-blind randomised controlled trial

Abstract: IntroductionTourette syndrome and chronic tic disorder are common, disabling childhood-onset conditions. Guidelines recommend that behavioural therapy should be offered as first-line treatment for children with tics. However, there are very few trained behaviour therapists for tics and many patients cannot access appropriate care. This trial investigates whether an internet-delivered intervention for tics can reduce severity of symptoms.Methods and analysisThis parallel-group, single-blind, randomised controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 43 publications
1
55
0
Order By: Relevance
“…1 . As they are expected, they will not be reported to the REC, in keeping with protocols established for other online studies [ 109 ]. All items in this list are specifically identified in the PIS as a possible harm of taking part in the trial so that potential participants can make an informed choice about participation: Feeling disconnected from others Feeling more pessimistic Feeling emotionally burdened Feeling inadequate Experiencing the release of uncomfortable emotions Engaging in harmful behaviours encountered in narratives.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 . As they are expected, they will not be reported to the REC, in keeping with protocols established for other online studies [ 109 ]. All items in this list are specifically identified in the PIS as a possible harm of taking part in the trial so that potential participants can make an informed choice about participation: Feeling disconnected from others Feeling more pessimistic Feeling emotionally burdened Feeling inadequate Experiencing the release of uncomfortable emotions Engaging in harmful behaviours encountered in narratives.…”
Section: Methodsmentioning
confidence: 99%
“…1. As they are expected, they will not be reported to the REC, in keeping with protocols established for other online studies [109]. All items in this list are specifically identified in the PIS as a possible harm of taking part in the trial so that potential participants can make an informed choice about participation:…”
Section: Safety Event Monitoring Response and Reportingmentioning
confidence: 99%
“…Furthermore, the return rate for this measure was comparable with the other measures, even though the requirement was for parents and teachers to complete it at all timepoints. Additionally, parents and clinicians in our previous workshops identified changes on the SNAP-IV as being the most meaningful outcome [38] Health economics questionnaires, RUSH and RUSE, were adapted from the CSRI [35] specifically for this study, to enhance the relevance of the questions to ADHD. The measures were co-designed by an expert in health economics (MJ), experts in ADHD (MG, KS, CH) and PPI representatives.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…A first pilot study on 23 patients has shown encouraging results in a rater-blind parallel group trial (including a 12 month follow up) 38 . A large (n= +200) UK-based study of ERP using this platform, called ORBIT, will commence shortly 39 .…”
Section: Treatmentmentioning
confidence: 99%